Erythropoietin use and abuse: When physiology and pharmacology collide - Spivak, J. L. (Advances in Experimental Medicine and Biology, 2001)
The major function of the erythrocyte is to transport oxygen from the lungs to the other tissues, a function ensured by the glycoprotein hormone erythropoietin which couples red cell production to long term tissue oxygen requirements. Tissue hypoxia is the only physiological mechanism for increasing erythropoietin production but there are a variety of mechanisms for its down regulation including hyperoxia, increased catabolism by an expanded erythroid progenitor cell pool, blood hyperviscosity independently of its oxygen content, renal disease and the cytokines produced in inflammatory, infectious and neoplastic disorders. Erythropoietin lack results in severe and often transfusion-dependent anemia but if bone marrow function is otherwise normal, recombinant human erythropoietin therapy can restore the red cell mass and alleviate the transfusion need. However, elevation of the red cell mass by recombinant human erythropoietin is associated with a reduction in plasma volume and in some patients, hypertension is induced. Elevation of the red cell mass is also associated with a reduction in cerebral blood flow. When used to gradually elevate the hematocrit to 36% in anemic patients, recombinant human erythropoietin therapy is usually uneventful. However, when the normal hematocrit level is exceeded, the risk for thrombotic events increases since blood viscosity varies exponentially with the hematocrit. Increasing the hematocrit by autologous blood transfusions can enhance athletic performance in fit individuals and recombinant human erythropoietin administration is an obvious surrogate for autologous blood transfusions. However, paradoxically, its effects are the opposite of those of endurance training, namely a change in red cell mass without an increase in the total blood volume. Thus, the use of recombinant human erythropoietin as a performance-enhancing agent is dangerous, particularly in the less fit athlete, and probably of little benefit in the highly conditioned one. Differences in the carbohydrate content of native and recombinant human erythropoietin are identifiable by isoelectric focusing, providing a direct means for detecting erythropoietin abuse using urine specimens; a panel of surrogate blood markers of enhanced erythropoiesis such as soluble transferrin receptors, serum erythropoietin, reticulocyte hematocrit and percent macrocytes provide an indirect means for this purpose. Timing of surveillance is, of course, critical due to biological limitations on the physical presence of the hormone. However, education about its dangers may prove to be the most valuable solution to abuse of recombinant human erythropoietin for competitive advantage.